Outcomes and Growth Patterns of Very Low Birth Weight Neonates Discharged from a Tertiary Care Hospital - Sangle, Dhananjay Arvind (Journal of Biomedical and Pharmaceutical Research, 2018)
Background: Very low birth weight (VLBW) neonates, defined as those weighing less than 1500 grams at birth, are at increased risk of various morbidities and mortality. Understanding the outcomes of these vulnerable infants is crucial for optimizing care and reducing complications. Objective: This study aims to evaluate the clinical outcomes of VLBW neonates discharged from a tertiary care hospital, focusing on neonatal morbidity, mortality, and growth patterns during the first year of life. Material and Methods: A total of 120 VLBW neonates discharged from the Department of Pediatrics at a tertiary care hospital were included in this retrospective study. Data on clinical outcomes, including neonatal morbidities, growth parameters, and follow-up visits, were collected and analyzed. Results: The study found a significant incidence of respiratory distress syndrome, infections, and feeding difficulties among the cohort. Follow-up growth parameters indicated a higher prevalence of undernutrition in the first year of life. Conclusion: VLBW neonates require meticulous care and follow-up to ensure optimal growth and development outcomes. Continuous monitoring of growth parameters and addressing associated morbidities can help improve the overall health of this population. Keywords: Very low birth weight, neonates, outcomes, neonatal morbidity, growth.